2014
DOI: 10.1088/1468-6996/15/5/055010
|View full text |Cite
|
Sign up to set email alerts
|

Precise control over shape and size of iron oxide nanocrystals suitable for assembly into ordered particle arrays

Abstract: Here we demonstrate how monodisperse iron oxide nanocubes and nanospheres with average sizes between 5 and 27 nm can be synthesized by thermal decomposition. The relative importance of the purity of the reactants, the ratio of oleic acid and sodium oleate, the maximum temperature, and the rate of temperature increase, on robust and reproducible size and shape-selective iron oxide nanoparticle synthesis are identified and discussed. The synthesis conditions that generate highly monodisperse iron oxide nanocubes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 46 publications
2
97
0
2
Order By: Relevance
“…All mentioned systems in this section contain long‐chain uncharged organic molecules as surfactants. There are three main ligands, which are used in the majority of the experiments: OA, OAm, and DDT (overview in Figure ). OA and OAm have the same carbon chain with 18 carbon atoms and a cis double bond at C9.…”
Section: Uncharged Organic Ligandsmentioning
confidence: 99%
“…All mentioned systems in this section contain long‐chain uncharged organic molecules as surfactants. There are three main ligands, which are used in the majority of the experiments: OA, OAm, and DDT (overview in Figure ). OA and OAm have the same carbon chain with 18 carbon atoms and a cis double bond at C9.…”
Section: Uncharged Organic Ligandsmentioning
confidence: 99%
“…A protocol for the formation of hollow silica cubes was presented by Rossi et al 18 In their work, they also demonstrated the formation of cubic crystals under attractive interactions by the addition of a depletant. 20 nm size from ion oleate precursors, Rossi et al 18 and Wetterskog et al 21 synthesized hematite superballs of ca. Magnetic cubes and superballs of different experimental origin have been synthesized and their properties in solution have been determined and complemented by simulation studies.…”
Section: Introductionmentioning
confidence: 99%
“…47 Briefly, in a 100 mL three-necked flask, 10 mmol of the iron oleate precursor is dissolved in 1-octadecene to obtain a volume of 50 mL and 8.85 mmol of eicosane, 0.25 mmol of oleic acid, and 0.25 mmol of sodium oleate are added under vigorous magnetic stirring. 47 Briefly, in a 100 mL three-necked flask, 10 mmol of the iron oleate precursor is dissolved in 1-octadecene to obtain a volume of 50 mL and 8.85 mmol of eicosane, 0.25 mmol of oleic acid, and 0.25 mmol of sodium oleate are added under vigorous magnetic stirring.…”
Section: Synthesis Of Fe 1-x O|fe 3-δ O 4 Nanocubes (Ioc)mentioning
confidence: 99%